Food scarcity and decrease in income are associated with depression after COVID-19 pandemic in rural settings - Gahwai, Dharmendra; Dayama, Sonal; Mishra, Aakanksha; Chandraker, Sandip Kumar; Sahu, Babita; Sharma, Mini; Kumar, Ravindra (Frontiers in Public Health, 2025)
ObjectiveThe current study is a cross-sectional survey that aims to assess an association COVID-19 on mental health in rural areas of Central India.MethodsGeneralized Anxiety Disorder Assessment (GAD-7), Patient Health Questionnaire (PHQ-9), and Impact of Events Scale-Revised (IES-R) were used to evaluate the anxiety, depression, and post-traumatic stress disorder (PTSD) among families with at least one member having been affected by COVID-19 during November 2022 to December 2022 in Durg District of Chhattisgarh State.ResultsA total of 431 participants were interviewed from 18 villages of Durg district of Chhattisgarh state. Symptoms of distress, anxiety and depression were observed in 26.2, 14.8 and 11.8% of participants. The death of family members due to COVID-19 and out of pocket expenditure was considerably associated with a higher risk of mental distress. A reduction in income was significantly associated with depression (p-value = 0.025, OR = 2.066, 95% CI = 1.115–3.817). Decline in income was also linked to depression among study participants (p value = 0.025, OR = 2.066, 95% CI = 1.115–3.817). Education, smoking and out of pocket expenditure was found be independently associated with occurrence of symptoms concerned with PTSD.ConclusionThe study points to the significance of socioeconomic factors like food security, and income stability during COVID-19 in mental health outcomes even after 1 year of pandemic. Increasing access to mental health resources and support for those affected by financial and food insecurities can help individuals cope with stress and maintain mental well-being.